Metabotropic glutamate receptors as drug targets for the treatment of absence epilepsy. (February 2018) - Ngomba, Richard Teke; van Luijtelaar, Gilles
Highlights: mGlu receptors are located within the cortico-thalamo-cortical system. mGlu receptors of all three subgroups are involved in the control of SWDs. mGlu5 receptor PAM has a good preclinical anti-absence profile. mGlu7 receptor seems to be an attractive target for putative anti-absence drugs. Abstract : Metabotropic glutamate (mGlu) receptors are expressed in key regions of the cortex and the thalamus and are known to regulate spike and wave discharges (SWDs), the electroclinical hallmarks of absence seizures. Recent preclinical studies have highlighted the therapeutic potential of selective group I and III mGlu receptor subtype allosteric modulators, which can suppress pathological SWDs. Of particular interest are positive allosteric modulators (PAMs) for mGlu5 receptors, as they currently show the most promise as novel anti-absence epilepsy drugs. The rational design of novel selective positive and negative allosteric mGlu modulators, especially for the mGlu5 receptor, has been made possible following the recent crystallographic structure determination of group I mGlu receptors. Our current knowledge of the role of different mGlu receptor subtypes in absence epilepsy is outlined in this article.